Caracterización química del camote toquecita en relación a la clasificación de tamaño y tratamiento térmico - Cuzme Delgado, Gema Nicole (2026)
The purpose of this research was to evaluate the chemical composition of toquecita sweet potatoes in relation to size classification and thermal treatment. A Completely Randomized Design was applied (CRD) with a factorial design A×B, with factorial arrangement 2x3 where Factor A: sweet potato size corresponds to medium (150–350 g) and baby (30–100 g), and Factor B: Cooking techniques included conventional cooking (92 °C for 40 min), microwave (1200 W for 8 min), and air fryer (160 °C for 15 min), resulting in six treatments with three repetitions. The response variables were carried out in three stages: determination of amylose, gravimetric ash analysis, and quantification of vitamin C and minerals through atomic absorption spectrophotometry. Data were analyzed using ANOVA with a level of significance of 5%. The results indicated no significant differences (p > 0.05) in amylose and ash content among treatments as well as in vitamin C and mineral levels. In conclusion, size classification and thermal treatment do not significantly modify the chemical composition of toquecita sweet potato, preserving its nutritional value under different cooking methods.